Peran Media Sosial Bawaslu dalam Meningkatkan Literasi Politik dan Partisipasi Politik Masyarakat - Novia Rahmadhani; Hari Juliansyah; Aprilnurrahmi . (CV. ITTC INDONESIA, 2025)
This study aims to explore the influence of social media content from the Election Supervisory Agency (Bawaslu) on political literacy and public participation in the political process in Indonesia, using the Media Literacy Theory as a conceptual framework. Through a combined approach of analyzing Bawaslu's social media content, surveys/questionnaires, and demographic data of respondents, this research highlights the positive impact of Bawaslu's social media content as a beneficial source of political information. The findings indicate that Bawaslu's social media content has enhanced access, analysis, evaluation, and production of political messages among the public. Additionally, the public responds positively to this content and perceives it as reliable. These results provide valuable insights for Bawaslu and stakeholders in optimizing the use of social media as a tool to improve political literacy and public participation in the political process in Indonesia